Kepemimpinan Multidimensi di Tengah Pandemi Covid 19 - Luqman Hadi (LP2M Sekolah Tinggi Agama Islam Nahdlatul Ulama Pacitan, 2021)
Leadership at the state level and at the level of business organizations over the past year has shown a change in the style of leadership that is most needed by each organization, namely strengthening leaders who have multidimensional capabilities. At the country level, we can see the emergence of leaders with multidimensional capacities, such as the leaders of Germany, New Zealand, China, to leaders in Scandinavian countries. Likewise, leadership at the level of business organizations is generally seen as prominent in managing and dealing with problems that arise due to the pandemic.